Manajemen Penguatan Pendidikan Karakter Islami melalui Program Keagamaan di Sekolah (JMPI: Jurnal Manajemen Pendidikan Islam, 2026)
This study aims to examine in depth the management of strengthening Islamic character education through religious programs in schools. The background of this research is based on the phenomenon of students’ character crisis and the suboptimal management of religious programs, which tend to be merely formalistic and have not significantly impacted behavioral development. This study employs a qualitative approach using a literature review method by analyzing various relevant scholarly sources. The data analysis technique utilizes content analysis, including data reduction, data presentation, and conclusion drawing, supported by source triangulation to ensure data validity. The findings indicate that the success of strengthening Islamic character is highly dependent on the quality of religious program management, which includes planning, organizing, and evaluation and supervision. In the planning aspect, the main issue lies in the lack of needs-based approaches and unclear orientation toward character transformation. In organizing, challenges are found in coordination and the limited involvement of all school stakeholders. Meanwhile, evaluation and supervision have begun to shift toward a more comprehensive approach but still face difficulties in measuring character aspects objectively. Therefore, systematic, integrated, and sustainable management of religious programs is necessary to effectively serve as an instrument for strengthening students’ Islamic character. Keywords: educational management, Islamic character, religious programs, school, character education